Implementasi Algoritma Naive Bayes pada Sistem Monitoring dan Klasifikasi Kualitas Air Akuarium Ikan Mas Koki - Agra Firmansyah; Dahnial Syauqy; Barlian Henryranu Prasetio (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
In this era of technological development, new innovations are needed that can help humans carry out their activities more efficiently. One of these areas of activity is measuring the water quality of the goldfish aquarium. At this time the measurement of air quality, especially in aquariums, is done manually on each attribute to be measured, while the measuring instrument for measuring the level of the attribute to be measured varies with prices that are relatively affordable to very expensive. In addition, using opinions based on direct observations of aquariums, etc. Therefore, the purpose of this research is to create a system that can help overcome this problem. In this study, the system was designed using a turbidity sensor as a measure of water turbidity levels, mq-135 as a measure of ammonia gas (NH3) and pH as a measure of acid and base levels. As for the display system using a 16x2 LCD to display the output obtained. This system component goes through the Arduino uno as a microcontroller and a laptop to enter code on the Arduino ide so that the system can run and as the main power supply. The classification used in this study is nave Bayes, nave Bayes is an algorithm method to determine the value of each class based on training data and test data, to read numerical attributes using distribution calculations, the attributes used in this Nave Bayes classification are obtained from reading turbidity, ammonia and ph of the sensor. This nave Bayes method has a fairly good accuracy, the higher the accuracy of the method, the more training data with various values.